Geochemistry and geochronology of the peripheral intrusions to the Kunene Anorthosite Complex in southern Angola and northern Namibia - Milani, Lorenzo (University of Pretoria, 2023)
Dissertation (MSc (Geology))--University of Pretoria, 2022.